Normative data for the squat, bench press and deadlift exercises in powerlifting: data from 809,986 competition entries - van den Hoek, D. J.; Beaumont, P. L.; van den Hoek, A. K.; Owen, P. J.; Garrett, J. M.; Buhmann, R.; Latella, C. (Journal of Science and Medicine in Sport, 2024)
Objective Strength assessment and comparison to normative values is an important benchmarking and diagnostic tool in human health and performance. However, population specific normative data is often several decades old, often lack information about adolescent and adult strength levels and are not representative of the strength levels of strength trained individuals. The purpose of this study was to develop contemporary strength norms for the squat, bench press, and deadlift using powerlifters competing in un-equipped, drug-tested competitions.